Land Use and Land Cover Change Analysis Using Google Earth Engine in Manamati Watershed of Kathmandu District, Nepal - Gautam, Lalmani; Rai, Raju (The Third Pole: Journal of Geography Education, 2022)
Understanding the changes in land use and land cover (LULC) is essential in managing and monitoring the resources and planning. This study has analyzed the LULC changes in the years between 1992 and 2017 in Manamati watershed, Kathmandu district. Google Earth Engine Java Script API has been used to prepare LULC database. The supervised classification of a maximum likelihood algorithm is also used to prepare LULC database. The result shows that more than 6% land of the cultivated area has been converted into built-up area from 1992 to 2017, and 2.43 km2 area has increased in built-up area. The forest-covered area seems to be constant, and it is not a significant change over the last 25 years. However, proper watershed management practice and land use planning require to control the threats to watershed resources. The results of this study could be a reference to the future planning of watershed resource management.